2016
DOI: 10.1093/jac/dkw477
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and characterization ofmcr-1-harbouringEscherichia coliisolated from pigs in Great Britain from 2013 to 2015

Abstract: mcr-1- harbouring plasmids were diverse, implying transposable elements are involved in mcr-1 transmission in GB. The low number of mcr-1 -positive E. coli isolates identified suggested mcr-1 is currently uncommon in E. coli from pigs within GB. The high sequence similarity between mcr-1 plasmid draft genomes identified in pig E. coli and plasmids found in human and livestock-associated isolates globally requires further investigation to understand the full implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 21 publications
0
39
0
Order By: Relevance
“…Following the report of mcr‐1 plasmid‐mediated colistin resistance in China, archived isolates and samples from animals have been screened for the presence of colistin‐resistant E. coli positive for mcr‐1 (Duggett et al . ). This screening resulted in mcr‐1‐ positive E. coli being detected from veterinary diagnostic submissions from two pig farms and in pigs from two unidentified farms sampled during anonymized monitoring of pigs at slaughter (Duggett et al .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Following the report of mcr‐1 plasmid‐mediated colistin resistance in China, archived isolates and samples from animals have been screened for the presence of colistin‐resistant E. coli positive for mcr‐1 (Duggett et al . ). This screening resulted in mcr‐1‐ positive E. coli being detected from veterinary diagnostic submissions from two pig farms and in pigs from two unidentified farms sampled during anonymized monitoring of pigs at slaughter (Duggett et al .…”
Section: Introductionmentioning
confidence: 97%
“…This screening resulted in mcr‐1‐ positive E. coli being detected from veterinary diagnostic submissions from two pig farms and in pigs from two unidentified farms sampled during anonymized monitoring of pigs at slaughter (Duggett et al . ). This study investigated one of the two identified pig farms longitudinally; previous reports have described the initial detection of mcr‐1 plasmids (Duggett et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Since a first report for the presence of the mcr-1 gene responsible for plasmid-mediated colistin resistance in commensal E. coli isolated in pig farms in China [43], the mcr genes have been reported among various bacterial pathogens worldwide [42]. Many reports showed that the same plasmids containing the mcr genes are detected in E. coli isolates from human and animals [44][45][46][47][48][49][50][51]. For example, some colistin-resistant E. coli strains isolated from commercial chicken meat in Brazil carried an IncX4 plasmid containing the mcr-1 gene [47] and the sequence of this plasmid showed 100% identity to that of another IncX4 plasmid (pICBEC72Hmcr), which is detected in a colistin-resistant E. coli strain isolated from human in Brazil [52].…”
Section: Observational Evidences For the Transmission Of Antibiotic Rmentioning
confidence: 99%
“…Enterobacteriaceae [59] Quinolone and fluoroquinolone Salmonella enterica [16] Escherichia coli [32] Sulfamethoxazole Salmonella enterica [16] Tetracycline Clostridium difficile [34] Multidrug Escherichia coli [33] Identification of the same genetic mobile element carrying the antibiotic resistance gene β-Lactam Escherichia coli [29,31,36,[60][61][62] Salmonella enterica [18,27,63] Colistin Escherichia coli [44][45][46][47][48][49][50][51] Salmonella enterica [64] Tetracycline Staphylococcus aureus [65] Environment and human Identification of the same antimicrobial-resistant strain β-Lactam Escherichia coli [35,41,66] Enterobacteriaceae [59] Multidrug Escherichia coli [40] Identification of the same genetic mobile element carrying the antibiotic resistance gene β-Lactam Enterobacteriaceae [67] Colistin Escherichia coli [53]…”
Section: Species Referencesmentioning
confidence: 99%